PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA APOTEK AS-SYIFA DI KALIWUNGU KENDAL - Fatechah, Natiqotul; Alfiah, Siti (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of service quality on consumer satisfaction, determine price on consumer satisfaction and determine service quality and price on consumer satisfaction who visit the As-syifa Kaliwungu Kendal Pharmacy. The type of research used is quantitative associative. The population in this study were consumers who visited the As-syifa Pharmacy Kaliwungu Kendal from January to December 2022 with a total of 98 samples used using the Slovin method. In collecting data using observation techniques and questionnaires, data analysis methods used SPSS version 26, multiple linear regression analysis, correlation coefficient test, coefficient of determination test, hypothesis testing (t test and f test). The results of the research state that there is a partial influence of service quality on consumer satisfaction with (tcount 15.517 > ttable 1.984 or a sig value of 0.000 and there is a partial influence of price on consumer satisfaction with (tcount 17.337 > ttable 1.984 or a sig value of 0.000 and there is an influence between service quality and price on consumer satisfaction are simultaneous with (fcount 181.954 > Ftable 3.09) with a significant value of 0.000. So the coefficient of determination obtained is 0.793 (79.3%). It can be concluded that service quality is 0.715 which can be interpreted as (Strong), and price quality is 0.758 which can be interpreted as (Strong).In this study, the results of multiple regression were obtained at Y = 3.787 + 0.366 + 0.655.